- Effects of Individualized Comprehensive Nutritional Support on Inflammatory Markers, serum amylase (AMS), prealbumin (PA), albumin (ALB), calcium ion (Ca2+) in Patients with Severe Pancreatitis: Nutritional Support on Inflammatory Markers, serum amylase (AMS), prealbumin (PA), albumin (ALB), calcium ion (Ca2+) - Meng, Wei (Journal of Medical Biochemistry, 2024)
Objective: To study the effectiveness of individualized comprehensive nutritional support on inflammatory markers, serum amylase (AMS), prealbumin (PA), albumin (ALB), calcium ion (Ca2+) in patients with severe acute pancreatitis (SAP). Methods: 102 participants with SAP treated in our hospital were chosen as the study objects. The participants were randomly split into control group and observation group, and both groups were given routine treatment. Observation group received individualized comprehensive nutrition support additionally. The inflammatory indexes, biochemical indexes and symptom improvement time were observed and analyzed on the day of admission, intervention 1d, intervention 3d, intervention 7d and intervention 14d. Results: Among the 102 patients included in this study, 3 cases had sudden exacerbation during the intervention, 1 case had clinical data missing >10%, and 1 case voluntarily withdrew due to personal factors, all of which were eliminated. Finally, the effective data of 97 patients were recovered. There were significant differences in the hypersensitive C-reactive protein (hs-CRP), white blood cell count (WBC), procalcitonin (PCT) and interleukin1β (IL-1β) between the two groups. The inter-group, time and interaction differences of AMS, PA, ALB and Ca2+ levels were significant different. The recovery time of abdominal pain, bowel sound, blood amylase level and urine amylase level in observation group was inferior to control group, and the differences were statistically significant (P
Keywords: severe acute pancreatitis; Individualized comprehensive nutrition support; Inflammatory index; Biochemical index; Vegetative state